SCMA CODEBOOK DESIGN BASED ON GRADIENT ASCENT ALGORITHM - Islam Kanatbekuli; Dmitriy Pokamestov; Yakov Kryukov; Eugeniy Rogozhnikov; Serafim Novichkov (Proceedings on Engineering Sciences, 2022)
Sparse Code Multiple Access (SCMA) is a non-orthogonal multiple access scheme, which improves spectrum efficiency. SCMA codebooks determine the bit error rate (BER) performance. There are various methods of constructing codebooks, but most of them are based on the formation of a mother constellation (MC). In this paper, we propose two methods to construct mother constellations with good characteristics, such as minimum Euclidian distance (MED) and peak-factor (PAPR). Also, we propose the method for optimizing user operators based on the Gradient Ascent Algorithm (GAA) to maximize the MED between superimposed codewords and superimposed constellation points. We consider the MCs built on various principles: rotation of the base constellation and interleaving; mapping of the golden angle modulation (GAM) points; mapping of the constellation points of existing modulation methods with interleaving The BER performance of the proposed methods outperforms existing codebook design schemes in uncoded SCMA systems. The proposed optimization method can be applied to arbitrary MC. The proposed methods for designing and optimizing codebooks can be used to build SCMA codebooks of different sizes with good characteristics.